Association between a 46-SNP Polygenic Risk Score and melanoma risk in Dutch patients with familial melanoma. Issue 11 (29th September 2020) - Potjer, Thomas P; van der Grinten, Tara W J; Lakeman, Inge M M; Bollen, Sander H; Rodríguez-Girondo, Mar; Iles, Mark M; Barrett, Jennifer H; Kiemeney, Lambertus A; Gruis, Nelleke A; van Asperen, Christi J; van der Stoep, Nienke
Abstract : Background: Familial clustering of melanoma suggests a shared genetic predisposition among family members, but only 10%–40% of familial cases carry a pathogenic variant in a known high-risk melanoma susceptibility gene. We investigated whether a melanoma-specific Polygenic Risk Score (PRS) is associated with melanoma risk in patients with genetically unexplained familial melanoma. Methods: Dutch familial melanoma cases (n=418) were genotyped for 46 SNPs previously identified as independently associated with melanoma risk. The 46-SNP PRS was calculated and standardised to 3423 healthy controls (sPRS) and the association between PRS and melanoma risk was modelled using logistic regression. Within the case series, possible differences were further explored by investigating the PRS in relation to (1) the number of primary melanomas in a patient and (2) the extent of familial clustering of melanoma. Results: The PRS was significantly associated with melanoma risk, with a per-SD OR of 2.12 (95% CI 1.90 to 2.35, p<0.001), corresponding to a 5.70-fold increased risk (95% CI 3.93 to 8.28) when comparing the top 90th to the middle 40–60th PRS percentiles. The mean PRS was significantly higher in cases with multiple primary melanomas than in cases with a single melanoma (sPRS 1.17 vs 0.71, p=0.001). Conversely, cases from high-density melanoma families had a lower (but non-significant) mean PRS than cases from low-density families (sPRS 0.60 vs 0.94, p=0.204). Conclusion: Our work underlines the significance of a PRS in determining melanoma susceptibility and encourages further exploration of the diagnostic value of a PRS in genetically unexplained melanoma families.